THE INFLUENCE OF WORLD OIL PRICES, EXCHANGE RATES, AND GLOBAL ECONOMIC UNCERTAINTY ON THE DYNAMICS OF THE COMPOSITE STOCK PRICE INDEX (IHSG) - Eza Syahbana; Fitrawaty Fitrawaty (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2026)
This study analyzes the effect of world oil prices, exchange rates, and global economic policy uncertainty on IHSG using the Error Correction Model (ECM). Secondary time series data are employed. The results show that in the short run all variables have a negative and insignificant effect on IHSG. In the long run, world oil prices and exchange rates have a positive and significant effect, while global economic policy uncertainty has a positive but insignificant effect. It is concluded that global factors exert short-term pressure but support stock market performance in the long term.